2022
DOI: 10.1002/ntls.20210089
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories and the perception of classical motion in the free propagation of wave packets

Abstract: The free propagation in time of a normalisable wave packet is the oldest problem of continuum quantum mechanics. Its motion from microscopic to macroscopic distance is the way in which most quantum systems are detected experimentally. Although much studied and analysed since 1927 and presented in many textbooks, here the problem is re-appraised from the standpoint of semi-classical mechanics. Particular aspects are the emergence of deterministic trajectories of particles emanating from a region of atomic dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…This generalises the result given in Ref. [6] for the ground state. It gives a new interpretation of the Gouy phase as the 'adiabatic' energy phase arising from the continuous propagation of the HO HG wave function.…”
Section: Quantum Mechanicssupporting
confidence: 92%
See 2 more Smart Citations
“…This generalises the result given in Ref. [6] for the ground state. It gives a new interpretation of the Gouy phase as the 'adiabatic' energy phase arising from the continuous propagation of the HO HG wave function.…”
Section: Quantum Mechanicssupporting
confidence: 92%
“…However, as shown in Ref. [6], the PE and TDSE are identical in that the approximation steps to derive the PE from the three‐dimensional Helmholtz equation are exactly those leading from the three‐dimensional time‐independent Schrödinger equation to the two‐dimensional TDSE.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Most recently, John Briggs applied the 1937 imaging theorem of Edwin Kemble [76] to the motion of atoms over macroscopic dis- tances such as those encountered in the SGE and concluded that the perception of classical (trajectories) or quantal (wavepackets) behavior depends on the accuracy of detecting the atoms' motion. Briggs' treatment is based on the assumption that the wavefunction always describes a statistical ensemble of identically-prepared particles and that no meaning can be ascribed to the wavefunction of a single particle [77,78]; it leads to the conclusion that the quantum-to-classical transition occurs due to a unitary evolution of the wavefunction. In contrast, decoherence theory [79][80][81][82] assumes a singleparticle wavefunction whose evolution is non-unitary due to environmental effects and whose collapse leads to a particular outcome of a measurement.…”
Section: Extended Wigner Fumentioning
confidence: 99%
“…[73] Most recently, John Briggs applied the 1937 imaging theorem of Edwin Kemble [74] to the motion of atoms over macroscopic distances such as those encountered in the SGE and concluded that the perception of classical (trajectories) or quantal (wavepackets) behavior depends on the accuracy of detecting the atoms' motion. Briggs' treatment is based on the assumption that the wavefunction always describes a statistical ensemble of identically-prepared particles and that no meaning can be ascribed to the wavefunction of a single particle; [75,76] it leads to the conclusion that the quantum-to-classical transition occurs due to a unitary evolution of the wavefunction. In contrast, decoherence theory [77][78][79][80] assumes a single-particle wavefunction whose evolution is non-unitary due to environmental effects and whose collapse leads to a particular outcome of a measurement.…”
Section: Quantum Theory Of the Stern-gerlach Experimentsmentioning
confidence: 99%